The Western Way? Democracy and the Media Assistance Model - Higgins, Daire (Global Media Journal - German Edition, 2015)
International media assistance took off during a time where the ideological extremes of USA vs. USSR were set to disappear. Following the Cold War, international relations focused on democracy building, and nurturing independent media was embraced as a key part of this strategy. Fukayama called it the ‘End of History’, the fact that all other ideologies had fallen and Western style democracy was set to become the one common ideology. The US and UK led the way in media assistance, with their liberal ideas of a free press, bolstered by free market capitalism. America was the superpower, and forged the way around the globe with its beacon of democracy. Under that guiding light they would bring truth, accuracy, freedom of expression and independent reporting to the countries which had so long lived under the shadow of communism, or authoritarian media systems. This is what propelled and justified American foreign policy, and their media assistance, for many years. Much work was thus carried out in Eastern Europe and the former Soviet satellites, but many now question the impact and legacy of these projects. When the US and UK spoke of media assistance they seemed to mean ‘free market’. These days, the ‘democracy promoters’ focus has turned more to Africa and the Middle East. The ideology is apparently the same: to help establish and support democracy with a stronger and more independent media. But with Western economies, and their media systems, in crisis, the relevance of this media assistance model is questioned. This essay looks at the history of media assistance and the ongoing debate on the impact of media assistance over the long term, its motives and the new balance of power appearing in international media development.